Excitation of electrostatic mode waves by hot electrons and ions in the plasmasphere - Singh V.; Singh R.N. (My University, 2025)
The analytical solutions of the general dispersion equation for ion acoustic and electron acoustic waves in two component cold plasma penetrated by a hot electron and a hot ion component represented by appropriate velocity distribution functions in the presence of collisions have been obtained. The expression for phase velocity, critical drift velocity for onset of instability and damping/growth rate have been derived. Using the various plasma and field parameters corresponding to L = 4 in the plasmasphere, we have computed various results using analytical expressions and we find that our results are in good agreement with the numerical solution of the general dispersion equation. Various features of electrostatic waves excited by streaming energetic electrons from equatorial region of the plasmasphere downwards, and by streaming ions from the polar ionosphere upwards into the plasmasphere has been studied. The diagnostic uses of these waves in the investigations of plasmaspheric region has been discussed. © 1989.